2007
DOI: 10.1900/rds.2007.4.44
|View full text |Cite
|
Sign up to set email alerts
|

Improved Monitoring of the Hyperglycemic State in Type 1 Diabetes Patients by Use of the Glycoalbumin/HbA1c Ratio

Abstract: Generally, the level of glycoalbumin (GA) is approximately 3 times higher than that of HbA1c. However, in type 1 diabetic patients, we often find an even higher GA/HbA1c ratio of nearly 3.5. Therefore, this study was performed to examine the significance of a higher GA/HbA1c ratio. METHODS: 17 type 1 diabetic patients were enrolled in part 1 of the study and divided into two groups, one with a higher and the other with a lower GA/HbA1c ratio. In both groups, the correlation between GA or HbA1c level and each "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 7 publications
2
13
2
Order By: Relevance
“…As limitations of this study, both GA and the GA/ A1C ratio are reported to be affected by diabetes type [19][20][21][22] and obesity [20,[22][23][24]. A similar tendency was also reported for the G-gap [6,7].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…As limitations of this study, both GA and the GA/ A1C ratio are reported to be affected by diabetes type [19][20][21][22] and obesity [20,[22][23][24]. A similar tendency was also reported for the G-gap [6,7].…”
Section: Discussionsupporting
confidence: 69%
“…However, given that approximately 50% of A1C is produced during the 30-35 days prior to measurement, both GA and A1C are affected by any significant alteration in plasma glucose during this period. The GA/A1C ratio may thus reflect worsening or improving fluctuations in glycemic control over the short term [21,22]. Some previous authors have argued that a high GA/A1C ratio is associated with postprandial glucose excursion, early progression to insulin therapy in type 2 diabetes, or other events [35,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that the improved glycemic control after switching from Lis to Glu is mainly attributable to the reduced postprandial glucose deviations owing to the above-mentioned differences in the PK and PD properties between Lis and Glu. Our hypothesis is also partly supported by the non-significant reduction in the GA/HbA1c ratio, known to be a marker for postprandial glycemic excursion [18] [19]. The significant improvement in patients' satisfaction indicated by the DTSQ was probably associated with the improvement in blood glucose level control and the convenience of the simultaneous injection of Glu and Gla using the same injection devices (SoloSTAR ® ).…”
Section: Discussionmentioning
confidence: 52%
“…22 Instead, HbA 1C is useful for the differential diagnosis of FT1DM and AT1DM, because HbA 1C levels are nearly normal or slightly elevated in FT1DM patients and, on the other hand, they are usually extremely high in AT1DM patients.…”
Section: Discussionmentioning
confidence: 99%